"Yo soy un gran visual". Juan Ramón Jiménez y la pintura. Issue 2 (2nd April 2020) - del Olmo Iturriarte, Almudena
Abstract: The consideration of the essential unity of all the arts is determinant in the esthetic ideology of Juan Ramón Jiménez. From this ideal of unity the poet proposes the breaking of limits between poetic, musical, and pictorial languages. This paper establishes the connection of his first books of poetry with painting; analyzes the uses of ekphrasis in Diario de un poeta recién casado and different portraits of painters in Españoles de tres mundos ; and also analyzes his personal relationships and varying opinions on different Spanish artists.